APLIKASI KECERDASAN EMOSIONAL DALAM PERILAKU ORGANISASI (SOCIETY, 2013)
Excellent human resources are required for organizational success in competition. Employees’ characters influence their behaviors. Therefore, emotional intelligence is essential for employees in order to be able to face challenges in their workplace. Every employee experiences a small or big pressure arising from her or himself, employment, colleagues, superiors or work environment. Emotional intelligence can be applied in many instances in an organization. However, this article focuses on the application of emotional intelligence in human relationship, motivation, leadership and misbehaviors in the workplace. In order to develop employeess’ emotional intelligence for organizational success, intensive professional training, relevant feedback and strong motivation for character development are required